La metrópoli de Simón Bolívar Centroamérica y el Caribe en disputa - Barboza Lizano, Óscar; Toribio Dantas , Alexis; Dembicz, Katarzyna (Ariadna Ediciones, 2019)
The presence of the Caribbean and Central America region in the past and present history of world power